Potent effects of dioscin against hepatocellular carcinoma through regulating TP53‐induced glycolysis and apoptosis regulator (TIGAR)‐mediated apoptosis, autophagy, and DNA damage. (18th March 2019) - Mao, Zhang; Han, Xu; Chen, Dahong; Xu, Youwei; Xu, Lina; Yin, Lianhong; Sun, Huijun; Qi, Yan; Fang, Lingling; Liu, Kexin; Peng, Jinyong
Abstract : Background and purpose: Dioscin shows potent effects against cancers. We aimed to elucidate its pharmacological effects and mechanisms of action on hepatocellular carcinoma (HCC) in vivo and in vitro. Experimental approach: Effects of dioscin were investigated in SMMC7721 and HepG2 cells, diethylnitrosamine‐induced primary liver cancer in rats, and cell xenografts in nude mice. Isobaric tags for relative and absolution quantitation (iTRAQ)‐based proteomics was used to find dioscin's targets and investigate its mechanism. Key results: In SMMC7721 and HepG2 cells dioscin markedly inhibited cell proliferation and migration, induced apoptosis, autophagy, and DNA damage. It inhibited DEN‐induced primary liver cancer in rats, markedly changed body weights and restored levels of α fetoprotein, alanine transaminase, aspartate transaminase, γ‐glutamyltransferase, alkaline phosphatase, and Ki67. It also inhibited growth of xenografts in mice. In SMMC7721 cells, 191 differentially expressed proteins were found after dioscin, based on iTRAQ‐based assay. TP53‐inducible glycolysis and apoptosis regulator (TIGAR) was identified as being significantly down‐regulated by dioscin. Dioscin induced cell apoptosis, autophagy, and DNA damage via increasing expression levels of p53, cleaved PARP, Bax, cleaved caspase‐3/9, Beclin‐1, and LC3 and suppressing those of Bcl‐2, p‐Akt, p‐ mammalian target of rapamycin (mTOR), CDK5, p‐ataxia telangiectasia‐mutated gene (ATM). The transfection of TIGAR siRNA into SMMC7721 cells and xenografts in nude mice further confirmed that the potent activity of dioscin against HCC is evoked by adjusting TIGAR‐mediated inhibition of p53, Akt/mTOR, and CDK5/ATM pathways. Conclusions and implications: The data suggest that dioscin has potential as a therapeutic, and TIGAR as a drug target for treating HCC.